2002
DOI: 10.1103/physreve.66.046401
|View full text |Cite
|
Sign up to set email alerts
|

Raman amplification of ultrashort laser pulses in microcapillary plasmas

Abstract: Experimental evidences of Raman amplification of ultrashort pulses in microcapillary plasmas are presented. The amplification of 100-500 fs pulses was investigated in microcapillaries with different lengths. The experimental data, together with simulation results, indicate that the resonance condition for Raman amplification in high-density plasma, n(e) approximately 1-3x10(20) cm(-3), existed only in a very short plasma column. Such an assumption makes it possible to reconcile the experimental results and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Recently, backscattered amplification was reported in a Li-F recombining plasma, 43 as well as in copper microcapillaries. 44 Resonant amplification appears to be observed as well in recent gas jet experiments. 45,46 However, a -pulse solution, or even any compression solution, has yet to be demonstrated in plasma.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, backscattered amplification was reported in a Li-F recombining plasma, 43 as well as in copper microcapillaries. 44 Resonant amplification appears to be observed as well in recent gas jet experiments. 45,46 However, a -pulse solution, or even any compression solution, has yet to be demonstrated in plasma.…”
Section: Discussionmentioning
confidence: 93%
“…For some time the main results obtained were an amplification by a factor 8 demonstrated for a plasma density of 3 × 10 20 cm −3 . Ping et al 18,19 observed gains of more than three orders of magnitude. However, they observed gain bandwidths, δλ/λ, less than 0.3% in the linear regime.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Previous experiments demonstrated low amplifications in a short microcapillary [13] and gas jet plasmas [14]. Recently, energy amplification of close to 100 was demonstrated in a plasma created in a 2 mm long gas jet with effective (i.e., with proper density) plasma length 1-1:5 mm.…”
mentioning
confidence: 99%
“…In this regime, the Raman amplification and compression of ultrashort pulses in a plasma allow intensities to reach 10 20 -10 21 W=cm 2 in a compact universityscale device, and unprecedented high intensity on the order of 10 25 W=cm 2 in a larger system [9]. Such intensities open new frontiers in physics and should also lead to practical applications such as fast ignition for inertial fusion [10], x-ray lasers [11], or laser wake field accelerators [12].Previous experiments demonstrated low amplifications in a short microcapillary [13] and gas jet plasmas [14]. Recently, energy amplification of close to 100 was demonstrated in a plasma created in a 2 mm long gas jet with effective (i.e., with proper density) plasma length 1-1:5 mm.…”
mentioning
confidence: 99%